Inflation in a scale-invariant universe - Ferreira, P; Hill, C; Noller, J; Ross, G (American Physical Society, 2018)
A scale-invariant universe can have a period of accelerated expansion at early times: inflation. We use a frame-invariant approach to calculate inflationary observables in a scale-invariant theory of gravity involving two scalar fields: the spectral indices, the tensor-to-scalar ratio, the level of isocurvature modes, and non-Gaussianity. We show that scale symmetry leads to an exact cancellation of isocurvature modes and that, in the scale symmetry–broken phase, this theory is well described by a single scalar-field theory. We find the predictions of this theory strongly compatible with current observations.